2003
DOI: 10.1023/a:1026387908165
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Cyclooxygenase-2 (COX-2) expression and certain growth hormones, such as gastrin, have been related to gastric carcinogenesis, but little is known about the factors that enhance this COX-2 expression and whether specific blockade of this enzyme has any influence on tumor growth and progression. Our objective was to determine the influence of a specific COX-2 inhibitor, rofecoxib (Vioxx), on serum and tumor levels of gastrin and its precursor, progastrin, as well as on tumor gene expression of COX-2, peroxisome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…253248 Given that CCK2R is expressed at higher levels in the stomach, 25 where a physiological role is well established, and that progastrin is overexpressed in some gastric cancers, 49 antagonising progastrin signalling could theoretically be effective as therapy in some distal gastric cancers. Nevertheless, we have also shown that amidated gastrin, the most abundant form of gastrin that signals through CCK2R, inhibits antral gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…253248 Given that CCK2R is expressed at higher levels in the stomach, 25 where a physiological role is well established, and that progastrin is overexpressed in some gastric cancers, 49 antagonising progastrin signalling could theoretically be effective as therapy in some distal gastric cancers. Nevertheless, we have also shown that amidated gastrin, the most abundant form of gastrin that signals through CCK2R, inhibits antral gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that COX-2 expression contributes to increased antiapoptotic, proangiogenic, and metastatic potential in cancer cells, and COX-2 deregulation is correlated with tumor progression (8,9). COX-2-derived PGE 2 stimulates angiogenesis via HIF-1␣, leading to the induction of vascular endothelial growth factor (10). Transcriptional up-regulation of the COX-2 gene by epidermal growth factor receptor (EGFR) and ErbB-2 has been found in cultured cancer cells (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Treatment of GC patients with rofecoxib (50 mg/day) resulted in a significant decrease in plasma and tumour contents of both progastrin and gastrin levels, and this was accompanied by the increased expression of proapoptptic proteins such as Bax and caspase-3 with a concomitant reduction in Bcl-2 and survivin expression. The blockade of COX-2 was also associated with a decrease in the serum level of proinflammatory cytokines IL-8 and TNFα being also involved in the gastric carcinogenesis [103]. …”
Section: Cyclooxygenase-2mentioning
confidence: 99%